Near-Zero Thermal Expansion and Phase Transitions in HfMg1−xZnxMo3O12 - Li, Sailei; Ge, Xianghong; Yuan, Huanli; Chen, Dongxia; Guo, Juan; Shen, Ruofan; Chao, Mingju; Liang, Erjun (Frontiers in Chemistry, 2018)
The effects of Zn2+ incorporation on the phase formation, thermal expansion, phase transition and vibrational properties ofHfMg1-xZnxMo3O12 are investigated by XRD, dilatometry and Raman spectroscopy. The results show that (i) single phase formation is only possible for x≤0.5, otherwise, additional phases ofHfMo2O8 and ZnMoO4 appear; (ii) The phase transition temperature from monoclinic to orthorhombic structure of the single phase HfMg1-xZnxMo3O12 can be well tailored, which increases with the content of Zn2+; (iii) The incorporation of Zn2+ leads to an pronounced reduction in the positive expansion of the b-axis and a enhanced negative thermal expansion in the c-axes, leading to a near-zero thermal expansion property with lower anisotropy over a wide temperature range; (iv) Replacement of Mg2+ by Zn2+ weakens the Mo-O bonds as revealed by obvious red shifts of all the Mo-O stretching modes with increasing the content of Zn2+ and improves the sintering performance of the samples which is observed by SEM. The mechanisms of the negative and near-zero thermal expansion are discussed.